PENCEMARAN SUNGAI SIAK DI KOTA PEKANBARU DAN PENEGAKAN HUKUM PIDANA LINGKUNGAN - Olivia Anggie Johar (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Enforcement of Environmental Criminal Law is one of the implementation processes of the utilization of principles, institutions, systems and criminal law sanctions to enforce environmental legal norms. The running or failure of the environmental criminal law enforcement process is very closely related to the settlement of the case. This can be illustrated from the pollution cases that occurred in the Siak River. Enforcement of Environmental Criminal Law must be done so that the Siak River is no longer a polluted river. Various kinds of laws and regulations concerning the protection of rivers from pollution both in the form of general regulations and specific arrangements are seen as not being able to control pollution of the Siak River in the city of Pekanbaru.